1999
DOI: 10.1021/ja991574a
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Bleomycin-Induced Alkali-Labile DNA Lesion

Abstract: Treatment of B-form DNA with the antitumor antibiotic bleomycin in the presence of Fe2+ and O2 affords both DNA strand scission and the formation of alkali-labile lesions, the proportion of which is quite sensitive to the concentration of O2 present. The alkali-labile lesions can undergo fragmentation cleanly in the presence of n-butylamine to afford DNA fragments containing 5‘- and 3‘-phosphate termini at the site of the alkali-labile lesion. The mechanism of decomposition of the alkali-labile lesion was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…The v 2 value of Eqn (18) used to perform a nonlinear least-squares analysis for the binding of BLM-A 5 to DNA is 0.0268, indicating a good appropriateness of the model proposed. The remaining standard thermodynamic parameters for the binding, D b G 0 m and D b S 0 m , are calculated by Eqns (19) and (20), respectively.…”
Section: Uv-vis Spectra Of Blm-amentioning
confidence: 99%
See 1 more Smart Citation
“…The v 2 value of Eqn (18) used to perform a nonlinear least-squares analysis for the binding of BLM-A 5 to DNA is 0.0268, indicating a good appropriateness of the model proposed. The remaining standard thermodynamic parameters for the binding, D b G 0 m and D b S 0 m , are calculated by Eqns (19) and (20), respectively.…”
Section: Uv-vis Spectra Of Blm-amentioning
confidence: 99%
“…It has been found that BLM-induced autoxidation of ferrous iron follows the Michaelis-Menten kinetics [9,10]. Although a significant number of experimental approaches have been used to elucidate the mechanism of DNA cleavage by BLM in the past two decades [2][3][4][5][6][11][12][13][14][15][16][17][18][19][20], thermodynamic information for the scission, which is necessary for a thorough understanding of the mechanism, is eagerly awaited. The purpose of this investigation is to provide detailed thermodynamic and kinetic data for BLMmediated DNA degradation to furnish insights into the anticancer mechanism of BLM.Microcalorimetry is an important tool for the study of both thermodynamic and kinetic properties of biological macromolecules by virtue of its general applicability, high accuracy and precision [21][22][23][24].…”
mentioning
confidence: 99%
“…This alkali lability has also been applied for footprinting experiments to analyze protein-DNA interactions in vivo (13,14). While the reactions of other alkali-labile DNA damages such as the apurinic/apyrimidinic (AP) site (15) and the bleomycin-induced lesion (16) have been analyzed in detail, the mechanism of the strand break caused at the (6-4) photoproduct by the alkali treatment has not been elucidated so far. Franklin et al (8) suggested the hydrolysis of the glycosyl bond of the 3Ј component of this photoproduct, but there have been no subsequent reports.…”
mentioning
confidence: 99%
“…15 We found that OAS reacted efficiently with a primary amine under mild conditions to yield lactam 4 and ODN fragments; this did not require additional reagents. [16][17][18] The ability of the 1,4-dicarbonyl system in 3 to form kinetically and thermodynamically favored 5-membered-ring aminal 5 19 results in facile lactam formation. We envisaged that bioconjugation of an ODN containing an OAS with lysine residues in close proximity to the C1-aldehyde and/or the C-4 ketone in the Scheme 1.…”
Section: Bioconjugation Of Oligodeoxynucleotides (Odns) With Biomolecmentioning
confidence: 99%